The Effect of Learning Organisation Practices in Cottage and Small Industries in Diktel Rupakot Majhuwagadhi Municipality - Rai, Bijaya Kumar (DMC Journal, 2025)
This study primarily aims to examine learning organisation practices, assess their effectiveness, and explore the relationships between the dimensions of learning organisation and the performance of cottage and small industries in Diktel Rupakot Majhuwagadhi Municipality (DRMM). In research methodology, a simple convenience sampling technique was used for primary data collection. The sample size was determined as158 using Yamane's formula (N/(1+N(e)2) with a fixed margin of error of 5 per cent, based on 260 registered and authentic firms. The administered questionnaire was distributed accordingly; however, only 127 respondents were received and deemed valid for analysis. The reliability and validity test of the collected data, as well as data processing and analysis, were conducted using IBM Statistical Packages for Social Sciences (SPSS) version 27 software. The findings of this study indicate that the multivariate test analysis is statistically significant (p